Chromium, Cadmium, Lead, and Arsenic Concentrations in Water, Vegetables, and Seafood Consumed in a Coastal Area in Northern Vietnam - Nguyen Thi Minh Ngoc; Nguyen Van Chuyen; Nguyen Thi Thu Thao; Nguyen Quang Duc; Nguyen Thi Thu Trang; Nguyen Thi Thanh Binh; Hoang Cao Sa; Nguyen Bao Tran; Nguyen Van Ba; Nguyen Van Khai; Ho Anh Son; Pham Van Han; et al. (SAGE Publishing, 2020)
Background: Heavy metal contamination and related risks for the environment and human health are matters of increasing concern. Methods: The levels of 4 heavy metals (Cr, Cd, Pb, and As) were evaluated in 2 water types (surface and well), 4 types of seafood (tiger shrimp, stuffed snail, snake-head fish, and catfish), and 27 types of vegetables (12 leafy vegetables, 4 pea plants, 4 tuber vegetables, and 7 herbs) that are commonly consumed in northern coastal communes located in Vietnam. Atomic absorption spectrometry was employed for quantification. Results: The mean concentrations of heavy metals detected in water, seafood, and vegetable samples exceeded the national permitted standards and World Health Organization (WHO) recommendation values by at least 2-fold, 2.5-fold, and 5-fold for surface water, vegetables, and well water, respectively. The concentrations of all 4 heavy metals detected in seafood samples were higher than the standards. The levels of heavy metals decreased with increasing distance between the sample collection point and the pollution source. Conclusions: This is the first report of heavy metal contamination of common sources of food and water in the northern coastal area of Vietnam. Significantly, the concentrations of heavy metals detected in study samples exceeded the regulatory limits. These results underscore the importance of continued monitoring and the development of intervention measures to ensure that the quality of food and water meets established standards and protects the health of the local population.